2022
DOI: 10.3390/nu14071355
|View full text |Cite
|
Sign up to set email alerts
|

The Challenges and Dilemmas of Interpreting Protein Labelling of Prepackaged Foods Encountered by the PKU Community

Abstract: Phenylketonuria (PKU) can lead to severe intellectual impairment unless a phenylalanine-restricted diet starts early in life. It requires expert user knowledge about the protein content of foods. The ability of adults or caregivers of children with PKU to calculate protein exchanges from food labels on manufactured foods and any difficulties they encounter in interpreting food labels has not been studied systematically. Individuals with PKU or their caregivers residing in the UK were invited to complete a cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…It is suggested that some children probably eat more protein than prescribed, even though they achieve acceptable blood Phe control [ 64 ]. Some teenagers who self-manage their dietary treatment may have little knowledge about the protein content of foods, and it has also been shown that both adults with PKU and caregivers have difficulties in interpreting food protein content from food labels and consequently only approximate the amounts of protein contained in food [ 66 ]. Some patients may also feel they cannot disclose their actual Phe/protein intake in case of disapproval from health professionals.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that some children probably eat more protein than prescribed, even though they achieve acceptable blood Phe control [ 64 ]. Some teenagers who self-manage their dietary treatment may have little knowledge about the protein content of foods, and it has also been shown that both adults with PKU and caregivers have difficulties in interpreting food protein content from food labels and consequently only approximate the amounts of protein contained in food [ 66 ]. Some patients may also feel they cannot disclose their actual Phe/protein intake in case of disapproval from health professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also shown a high rate (>50%) of protein-labelling errors (e.g., unclear, misleading, inaccurate, or incomplete information) affecting interpretation of protein content of packaged manufactured foods on supermarket websites [34]. Ninety per cent of patients with PKU or their caregivers reported that they experienced problems with food labelling e.g., difficulties with interpreting food protein exchanges from food labels or labels containing misleading or confusing information [35].…”
Section: Introductionmentioning
confidence: 99%